Cytotoxic xanthonoids from the stem bark of Garcinia hanburyi collected in Vietnam - An, Nguyen Thi Kim; Quang, Ngo Dai; Long, Pham Quoc; Thuy, Tran Thi Thu (Vietnam Journal of Science and Technology, 2020)
Five prenylated caged xanthones, desoxymorellin, morellic acid, gambogic acid, isogambogic acid and 10α-butoxy gambogic acid , were isolated from the stem bark of Garcinia hanburyi collected in Vietnam. Their structures were elucidated by detailed 1D, 2D NMR spectroscopic analyses and comparison with reported data. Two major constituents, gambogic acid and isogambogic acid, displayed strong cytotoxicity against LLC and SK-LU-1cell lines with IC50 values in the range from 0.35±0.05 µM to 2.26±0.19 µM. This is the first study on the cytotoxicity of gambogic acid and isogambogic acid against LLC and SK-LU-1 lung cancer cell lines.